A Visit to Rusty Ships. Tourism as a Strategy of Rejuvenating Shrinking Towns in Coastal Areas. (1st September 2021) - Jarosz, Katarzyna; Tricoire, Hanna Daria
The aim of the paper is to analyse, whether and to what degree that tourism is a way of rejuvenating shrinking cities located on the coast. The research is based on three cities, and the adjacent regions, located in Uzbekistan (Mo'noq), Romania (Sulina) and Georgia-Abkhazia (Sukhumi). Tourist attractions connected with nature, culture, history and cuisine are examined, along with the land use and tourist infrastructure. The research indicates that the three sites have great tourism potential, with a focus on nature-oriented tourism. It also suggests that infrastructure, transport, access to information and land use can have a strong, positive or negative impact on tourism attractiveness. Additionally, the threats that uncontrolled tourism can bring are considered - it has been shown that unsustainable tourism and an excessive influx of tourists are threats to the environment and to local societies. A balance between economic and environmental value should therefore be maintained in the process of developing tourism.